2012
DOI: 10.1186/1742-2094-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of microglial cells in the hippocampal dentate gyrus of Gunn rat: a possible schizophrenia animal model

Abstract: Background: Schizophrenia is a debilitating and complex mental disorder whose exact etiology remains unknown. There is growing amount of evidence of a relationship between neuroinflammation, as demonstrated by microglial activation, and schizophrenia. Our previous studies have proposed that hyperbilirubinemia plays a role in the pathophysiology of schizophrenia. Furthermore, we suggested the Gunn rat, an animal model of bilirubin encephalopathy, as a possible animal model of schizophrenia. However, the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 48 publications
(56 reference statements)
4
38
0
1
Order By: Relevance
“…The results of this study indicating that both microglia and astrocytes are significantly activated in the hippocampus of Gunn rats as shown by immunohistochemistry using Iba1 and S100B are consistent with our previous studies which demonstrated increased immunoreactivity for another microglial marker CD11b (Furuya et al., 2013; Liaury et al., 2012, 2014) and for another astrocytic marker GFAP (Limoa et al., 2016) in the hippocampal DG, CA1, and CA3. These observations of the increased immunoreactivity using two distinct markers for each glial cell substantiate both microglial activation and astrocytic activation in the hippocampus of Gunn rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicating that both microglia and astrocytes are significantly activated in the hippocampus of Gunn rats as shown by immunohistochemistry using Iba1 and S100B are consistent with our previous studies which demonstrated increased immunoreactivity for another microglial marker CD11b (Furuya et al., 2013; Liaury et al., 2012, 2014) and for another astrocytic marker GFAP (Limoa et al., 2016) in the hippocampal DG, CA1, and CA3. These observations of the increased immunoreactivity using two distinct markers for each glial cell substantiate both microglial activation and astrocytic activation in the hippocampus of Gunn rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Gunn rats have been used as an experimental model of kernicterus (bilirubin encephalopathy), which can be considered as an organic brain disorder. As patients with organic brain disorder often present symptoms of schizophrenia and affective disorder (Hamilton, Frick, Takahashi, & Hopping, 1983), it is not unexpected that Gunn rats show depression‐like behavior as demonstrated by this study and schizophrenia‐like behavior as shown by our previous studies (Furuya et al., 2013; Liaury et al., 2012, 2014; Limoa et al., 2016). It has been shown that a neuronal damage in the hippocampus is caused by unconjugated bilirubin in growing Gunn rats (Ohno, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iba-1 positive cells were counted as previously described 26 . To estimate the number of Iba-1 labeled microglia, images were taken using a light microscope (Nikon Eclipse 90i).…”
Section: Quantification Of Microgliamentioning
confidence: 99%
“…Collectively, disrupted axonal transport, ionic imbalance, and mitochondrial dysfunction can lead to axonal swelling 8,[22][23][24][25][26] , plasma membrane disruption, and release of intracellular contents, including mitochondria. The latter can act as damage associated molecular patterns and lead to recruitment or activation of inflammatory cells 48 .…”
Section: Journal Of Neurotraumamentioning
confidence: 99%